Physical stability of pellets protected by different waterproofed products - Pezzato, Luiz Edivaldo; Moura, Monica Accaui Marcondes; Barros, Margarida Maria; Pezzato, Antonio Celso; Cantelmo, Osmar Angelo (Pesquisa Agropecuaria Brasileira, 1997)
In the Fish Nutrition Laboratory of the Department of Genetic Improvement and Animal Nutrition (FMVZ, UNESP - Botucatu Campus), three ingredients were utilized as coat for commercial pelleted diet, and were compared in regard to waterproofing capacity and to its relation with physical stability when in contact with water. A commercial pelletized diet was utilized for tropical fish (26% crude protein), whose treatments were characterized by application of a coating bath giving origin to the treatments: commercial ration; commercial ration + gelatine coat; commercial ration + fish oil and, commercial ration + gelatinized corn starch. The fish oil proved to be the best ingredient for coating of pelletized diets for aquatic organisms, to improve their physical stability in water; the fish oil may be added to commercial pelletized diets as a chemitherapeutic vehicle, without any damage to the management adapted; and, when necessary, since it is correctly applied, the coating bath can be utilized without damage to the physical characteristics of pellets.